2005
DOI: 10.1074/jbc.m410947200
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Refolding of Aggregation-prone Citrate Synthase by Polyol Osmolytes

Abstract: Efficient refolding of proteins and prevention of their aggregation during folding are of vital importance in recombinant protein production and in finding cures for several diseases. We have used citrate synthase (CS) as a model to understand the mechanism of aggregation during refolding and its prevention using several known structure-stabilizing cosolvent additives of the polyol series. Interestingly, no parallel correlation between the folding effect and the general stabilizing effect exerted by polyols wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 69 publications
2
56
0
Order By: Relevance
“…Consistent with our in vivo results, they found that glycerol and sorbitol were the most effective as osmolytes, with 2 M and 7 M glycerol enhancing CS refolding yield 1.5-and 2.25-fold, respectively. Sorbitol at 1 M was also effective, enhancing CS refolding yield 1.5-fold [10]. Like us, they also observed that ethylene glycol and erythritol were less effective as osmolytes than glycerol or sorbitol.…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…Consistent with our in vivo results, they found that glycerol and sorbitol were the most effective as osmolytes, with 2 M and 7 M glycerol enhancing CS refolding yield 1.5-and 2.25-fold, respectively. Sorbitol at 1 M was also effective, enhancing CS refolding yield 1.5-fold [10]. Like us, they also observed that ethylene glycol and erythritol were less effective as osmolytes than glycerol or sorbitol.…”
Section: Resultssupporting
confidence: 59%
“…Further, Mishra et al observed a very poor correlation between osmolyte concentration and refolding yield [10]. Higher concentrations of osmolytes in general were found to actually decrease citrate synthase refolding yields and, as noted, some osmolytes like erythritol even decreased folding yields at all concentrations tested.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The expression vector was transformed into E. coli BL21(DE3) cells, grown at 37°C in LB medium until the optical density achieved 12 at 600 nm. The 3% (vol/vol) ethanol was added during expression for inducing the endogenous chaperones of E. coli to assist the recombinant protein folding (48). The expression of GST-FIN219 proteins was induced by 0.1 mM isopropyl β-D-1-thiogalactopyranoside (IPTG) for 18 h at 16°C.…”
Section: Methodsmentioning
confidence: 99%